Estratégias de evasão do Sistema do Complemento em protozoários parasitos: revisitando antigos conceitos e proposição de uma nova forma de escape - Laura Valeria Rios Barros (2021)
Parasitic protozoa are unicellular eukaryotic organisms capable of developing intra and extracellular parasitism in numerous species of living beings. In humans, these parasites cause diseases with a great impact on public health. The success of a parasite in establishing the infection depends on a series of intricate evolutionarily selected adaptations, which include the development of molecular and cellular strategies that allow the evasion of the effector mechanisms of the immune system of its hosts. The complement system is one of the main branches of innate immunity in mammals and other organisms, and therefore it is at the forefront in the fight against invading parasites. It is a set of effector molecules that act in a finely regulated manner and whose purpose is the extermination of the invading species. For unicellular parasites, such as protozoa, bacteria and some fungi, the final activation of the complement system culminates in the elimination of the pathogen via cell lysis, through the formation of a lytic pore that depolarizes the plasmatic membrane of the parasite. Different strategies of resistance to attack by the complement system have been reported for the different species of known protozoan parasites, among them: 1- sequestration of regulatory proteins of the complement system produced by the host itself, 2- expression of regulatory proteins of the complement system by the parasite, 3- proteolytic destruction of different factors by membrane proteases expressed by the parasite, 4- formation of a physical glycolipid barrier that prevents the deposition of molecules from the complement system directly on the plasmatic membrane of the parasite, and 5- removal, by endocytosis, of effector molecules of the complement system linked to the plasmatic membrane of the parasite. In this work, we review the different resistance strategies to the complement system described for the main species of protozoan parasites and propose a new escape mechanism using Leishmania amazonensis as a model. Our findings show that the promastigote forms of the parasite are able to remove the lytic pore formed by the final activation of the human complement system. Indeed, the ability to repair damage inflicted on the plasma membrane is an ancestral mechanism present in eukaryotic cells. Together with findings from other groups, our data indicate that parasitic protozoans have preserved this ancestral cellular mechanism and that it can be used as a defense against attack by lytic pores in the complement system of their hosts, in an unprecedented example of evolutionary exaptation.